Fetal central nervous system anomalies according to RT‐PCR and trimester of maternal infection with Zika virus: A prospective cohort study - Luz Ángela Gutiérrez‐Sánchez; Carlos Hernán Becerra‐Mojica; Mario Augusto Rojas; Luis Alfonso Díaz‐Martínez; Luis Alfonso Pérez Vera; Gustavo Adolfo Contreras García; Luz Stella Pinilla García (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction In October 2015, an epidemic of Zika began in Colombia’s geographic areas with a high population of mosquitoes of the genus Aedes. We aimed to describe the fetal brain ultrasound findings in pregnant women with active symptoms or a history of symptoms suggestive of Zika virus (ZIKV) infection. Material and methods Eligible pregnant women were tested with reverse transcriptase‐polymerase chain reaction (RT‐PCR) for ZIKV and followed prospectively using detailed anatomic ultrasound and transvaginal neurosonography to detect structural anomalies of the fetal central nervous system (CNS). Results A total of 115 symptomatic women with a positive ZIKV RT‐PCR and 55 with a negative ZIKV RT‐PCR were enrolled in the study; CNS compromise of the fetus occurred in 22% and 17%, respectively (p = 0.255). Callosal dysgenesis (14.5%) was the most frequent anomaly of the CNS, followed by microcephaly (13.6%) and neuronal migration disorders (8.3%). When symptomatic ZIKV RT‐PCR‐positive women were categorized by trimester of infection, CNS anomalies were present in 40% of first‐trimester infections, compared with 21% and 7% in second‐ and third‐trimester infections (p = 0.002). CNS anomalies were also more severe in first–trimester‐infected fetuses than in second– and third–trimester‐infected fetuses. The high prevalence of CNS anomalies in fetuses of symptomatic ZIKV RT‐PCR negative women suggests a high rate of false‐negative cases and an even higher prevalence of CNS anomalies than observed in this study. Conclusions The prevalence of fetal CNS anomalies was higher than previously reported in the literature for both symptomatic RT‐PCR‐positive and ‐negative pregnant women. Corpus callosum anomalies, microcephaly, neuronal migration disorders, and brain parenchymal hyperechogenicities were the most frequent CNS anomalies detected. In addition, CNS anomalies were more frequent and severe in infected fetuses during the first trimester of pregnancy than during the second or third trimester.